STRATEGY OF PARTNERSHIP MANAGEMENT IN THE STRENGTHENING OF SUPPLY CHAIN IN THE NEW NORMAL ERA - I Made Donna Sinarjaya; I G N Putra Suryanatha (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
The research was made aiming to find out the partnership strategy and the Jembrana Eel SMEs supply chain. The research method uses qualitative interviews with the six MSMEs in Jembrana Regency. The results of this study resulted in a partnership improvement strategy, in the Jembrana Eel SMEs supply chain using SWOT analysis. Product development in new innovative ideas in the form of processed shredded eel to add product variety in promoting to consumers. SMEs are expected to maximize social media for the process of introducing products and increasing sales turnover. Creating products that are used sustainably and are beneficial to consumers.